Phosphorus in Acid Soils Amended with Organic and Inorganic Inputs: its Status and Interactions - Bah, Abdul Rahman (2002)
The combined use of green manures (GMs) and phosphate rocks (PRs) could be a more efficient and sustainable approach in alleviating P deficiency in acid tropical soils. Understanding the chemical and biological processes or interactions influencing P dynamics in such systems is therefore, vital for adaptation to different cropping systems. The effect of GMs and P fertilizers on two acid soils (Bungor and Selangor series) was investigated in a laboratory incubation study and two glasshouse experiments using conventional and radioisotope techniques. The treatments were a factorial combination of GMs (legumes - Calopogonium caeruleum, Gliricidia sepium, and a non-legume Imperata cylindrica) and P fertilizers (PRs from North Carolina, China and Algeria, and triple superphosphate), completely randomized with up to 4 replications. Olsen P, biomass P, exchangeable Ca, mineral N and acidity were monitored in the soils for 16 months, and P in the soil fractions/pools was quantified at the end of the incubation. The relative contribution of the sources to P uptake and utilization by Setaria grass (Setaria sphacelota) was determined by the 33p.32p double isotope labeling and 32p isotope dilution techniques. The P fertilizers had little effect on available P, whilst the sole GMs and GM+P amendments altered it in two phases. An initial lag phase with depressed P levels in the first 16 weeks coincided with the buildup of NH4-N (up to 1000 mg N kg-') and exchangeable Ca, elevated soil pH (up to 2.3 units), up to 5-fold increase in microbial P, and significant GMxPxSoil interactions. The second phase showed higher available P, and much lower NH4-N, biomass P, pH. The GMs also reduced sorption capacity (by over 84%), increased available P 6-10 times, and also the AI-P and Fe-P fractions. They decreased P in the unavailable pool, the organic-P fraction and 50-75% of Ca-P in PR-amended soils. The GM contribution to P uptake was small «5%) and the utilization was <1%, but they caused much higher total P uptake than the P fertilizers alone (more than 160%). They improved fertilizer-P utilization from <20% to >50%. They significantly enhanced soil P contribution in the following order: Gliricidia<lmperata<Calopogonium. Unexpectedly, the low quality Imperata GM also increased P availability and uptake when integrated with reactive PRs, probably by improving soil moisture content. Calcium concentration, GM quality, microbial turnover, and soil P mobilizing capacity regulated P dynamics in these systems.